2014
DOI: 10.1016/j.amjcard.2014.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Sarcomere Gene Mutations Analysis in the End-Stage Phase of Hypertrophic Cardiomyopathy

Abstract: End-stage hypertrophic cardiomyopathy (ES-HC) has an ominous prognosis. Whether genotype can influence ES-HC occurrence is unresolved. We assessed the spectrum and clinical correlates of HC-associated mutations in a large multicenter cohort with end-stage ES-HC. Sequencing analysis of 8 sarcomere genes (MYH7, MYBPC3, TNNI3, TNNT2, TPM1, MYL2, MYL3, and ACTC1) and 2 metabolic genes (PRKAG2 and LAMP2) was performed in 156 ES-HC patients with left ventricular (LV) ejection fraction (EF) <50%. A comparison among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 27 publications
4
57
0
4
Order By: Relevance
“…They found 3 patients from 2 families who were homozygotes for a P/LP variant. Biagini et al 9 found that 13 out of 156 patients (13%) with end-stage HCM had >1 pathogenic variant; however, the details of variants were not available for evaluation.…”
Section: Case Reports and Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found 3 patients from 2 families who were homozygotes for a P/LP variant. Biagini et al 9 found that 13 out of 156 patients (13%) with end-stage HCM had >1 pathogenic variant; however, the details of variants were not available for evaluation.…”
Section: Case Reports and Seriesmentioning
confidence: 99%
“…7,8 Specifically, an earlier disease onset, more severe left ventricular hypertrophy, higher prevalence of advanced heart failure, 9 and increased risk of sudden cardiac death (SCD) 10 have all been reported in patients with double mutations. These associations, however, are based on relatively small series and case reports and in most cases rely on genetic variant classification before the age of large exome databases.…”
Section: See Editorial By Fatkin and Johnson See Clinical Perspectivementioning
confidence: 99%
“…3 These patients may never become candidates for aggressive therapeutic options such as heart transplantation (HT). [12][13][14][15][16] Conversely, young HCM patients with restrictive evolution may develop severe HF requiring aggressive management despite LVEF values well above 50%. 13 Therefore, the overall burden of advanced HF related to HCM progression, defined by clinical rather than instrumental indices of cardiac dysfunction, remains unresolved.…”
mentioning
confidence: 99%
“…На самом деле пациенты с ФВ ЛЖ менее 50 % могут иметь невыраженные симпто-мы ХСН с медленным их прогрессированием до пожи-лого возраста. Эти пациенты могут никогда не попадать на трансплантацию сердца (ТС) [7,8]. И наоборот, моло-дые пациенты с замедленным прогрессированием ХСН могут иметь симптомы выраженной ХСН, требующей агрессивного лечения, несмотря на ФВ ЛЖ более 50 % [9].…”
Section: Discussionunclassified